Evaluation of 5-methyl-2´-deoxycytidine stability in hydrolyzed and nonhydrolyzed DNA by HPLC–UV. (February 2012) - Kovatsi, Leda; Fragou, Domniki; Samanidou, Victoria; Njau, Samuel; Kouidou, Sofia; Bailey, Alexis
Background: Although the determination of 5-methyl-2´-deoxycytidine (5-MedC) in various biological samples is gaining increasing scientific interest, there are no data available regarding its stability.Results: We have currently evaluated the stability of 5-MedC and 2´-deoxycytidine (dC) at -20°C, both in hydrolyzed and nonhydrolyzed calf thymus DNA (CT DNA), as well as following repetitive freeze–thaw cycles. HPLC–UV was used for the accurate determination of the two 2''-deoxynucleosides. Statistical evaluation of the results revealed that 5-MedC and dC were stable in hydrolyzed CT DNA for at least 7 days and in nonhydrolyzed CT DNA for at least 65 days, when these were stored at -20°C. Furthermore, both 2''-deoxynucleosides were stable for at least three repetitive freeze–thaw cycles.Conclusion: By using HPLC–UV, we have evaluated the stability of 5-MedC and dC under storage conditions and repetitive freeze–thaw cycles. Our results are informative about the way samples should be handled and stored in epigenetic studies.